Wanted -- Focused Leadership Theory and Application in Public Health Professional Preparation - Robert J. McDermott (University of North Florida, 2008)
Many faculty and administrators in academic public health believe that professional preparation culminating in the awarding of the MPH degree is necessarily coupled with the development of leadership skills and dynamic leaders. This assumption may indeed be a false one. Integrating specific leadership paradigms into public health professional preparation and applying leadership theory to specific public health problems may assist the leadership development process and increase the possibility that professional preparation and the acquisition of leadership knowledge and skills are more intimately entwined.